TOURISM VILLAGE DEVELOPMENT IN COMMUNITY EMPOWERMENT EFFORT (Empowering Local Community through School-Community-based Education) - Tatu Mesaroh; Omah Mukarromah (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2022)
Pandeglang is one of the tourist cities that is a destination for tourists, both local and foreign tourists. In view of this, STKIP Syekh Manshur Research and Community Service Center (P3M) along with the Elementary School Education Study Program conducted research related to the development of tourist villages in developing and empowering the community. This research was conducted in a qualitative method by dividing it into three stages; data reduction, organization and interpretation of data. Data reduction was carried out to identify the raw data obtained through observation and interviews. Organizing is done to collect and unify data information obtained from the results of the initial identification (data reduction process) which is then interpreted to produce a conclusion as clearly discussed in the manuscript.